2014
DOI: 10.1108/jmhtep-04-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

“The college is so different from anything I have done”. A study of the characteristics of Nottingham Recovery College

Abstract: Purpose – This paper aims to describe the working of one of the first Recovery Colleges (RCs) and explore the defining characteristics. Design/methodology/approach – This study explores the ways in which an educational approach contributes to the process of recovery as observed in the Nottingham Recovery College (NRC). A mixed-method research design was adopted, combining interviews, observation and visual methods as well as analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 6 publications
5
90
0
Order By: Relevance
“…Some descriptive research has examined the defining characteristics, core values and central features of recovery colleges. These are mostly single‐site case studies, which have been compared for shared themes in two recent systematic literature reviews. These studies indicate several common core characteristics across recovery colleges.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Some descriptive research has examined the defining characteristics, core values and central features of recovery colleges. These are mostly single‐site case studies, which have been compared for shared themes in two recent systematic literature reviews. These studies indicate several common core characteristics across recovery colleges.…”
mentioning
confidence: 99%
“…First, recovery colleges tend to be based on the theory and practice of adult education, rather than clinical or therapeutic models. As such, they possess many of the core characteristics of an adult education college: registration, enrollment, term curricula, full‐time staff, sessional teachers and a yearly cycle of classes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the need for RC outcomes to be defined remains pivotal to development (Meddings et al 2015b;McGregor et al 2016), a collection of studies have highlighted the benefits of RC attendance for students and the organisation in which they are located (Zabel et al, 2016); with Meddings et al (2015b) concluding that attendance at the RC has consistently been found to be useful, and help people progress towards their recovery goals. However, as noted by McGregor et al (2014), the crucial elements of RCs need to be further explored.…”
mentioning
confidence: 99%